ANALYSIS OF INSTRUCTIONAL LEADERSHIP MODELS IN ISLAMIC RELIGIOUS EDUCATION MANAGEMENT - Rabbi, Mim Fadhli; Hermina, Dina; Mof, Yahya (STKIP PGRI Situbondo, 2024)
This research examines instructional leadership models in educational contexts, focusing on transformational, transactional, and Islamic value-based approaches. A comprehensive literature study explored the complex dynamics of contemporary educational leadership. The research demonstrates that each leadership model possesses unique characteristics influencing organizational effectiveness. Transformational leadership highlights structural inspiration and motivation, while transactional leadership emphasizes exchange mechanisms and incentives. The Islamic value-based model integrates spiritual dimensions and moral ethics in leadership practices. Findings indicate the importance of a holistic approach that synergizes managerial, psychological, and spiritual aspects in building a dynamic and high-quality educational ecosystem. Research implications emphasize the need for adaptive leadership models capable of responding to the complexity of contemporary educational challenges.